THE TOURISM ECONOMIC IMPACT FROM APPLIED OF COMMUNITY BASED TOURISM CONCEPT (STUDY IN KUIN TOURISM VILLAGE BANJARMASIN, SOUTH KALIMANTAN) - Dewi Rahayu; Ika Chandriyanti; Noor Rahmini (UNEJ e-Proceeding)
The objectives of the research are (1) To identify and map the application of Community Based Tourism (CBT) concept in Kuin Tourism Village and (2) to analyze the economic benefits created from the application of Community Based Tourism concept in Kuin Tourism Village. Types of research are descriptive quantitative and qualitative case studies. Methods of data collection is done by documentation and interviews. The results showed that the economic impacts derived from the application of Community Based Tourism in Kuin Tourism Village are direct impacts, indirect impacts, and follow-up impacts. The direct impacts are development of restaurant or shop business around the location of tourist attractions, employment, the development of vessel rental services and parking services. The indirect impacts are of the development of SMEs making river fish crackers, culinary business soto banjar, and handicrafts tanggui. The follow-up impacts are the better access road and the availability of a representative dock.